2011
DOI: 10.1038/labinvest.2011.82
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis study of enterovirus 71 infection in rhesus monkeys

Abstract: Enterovirus 71 (EV71), a major pathogen that is responsible for causing hand-foot-and-mouth disease (HFMD) worldwide, is a member of the Human Enterovirus species A, family Picornaviridae. HFMD that is caused by EV71 is usually characterized by vesicular lesions on the skin and oral mucosa and high morbidity rates in children; additionally, occasional fatal cases have been reported involving brainstem encephalitis and myelitis associated with cardiopulmonary collapse. Although viral pathogenesis in humans is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
85
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 31 publications
13
85
1
Order By: Relevance
“…The ability to further our knowledge of EV71 and to develop effective prophylactic and therapeutic approaches has been severely hampered by the lack of a relevant animal model, a deficit resulting from the limited species tropism of EV71. Experimental infection of rhesus and cynomolgus monkeys has been reported, but their use is limited for ethical and economical reasons (6,15,17,41). Furthermore, EV71-infected monkeys do not develop any typical neurological complications, including flaccid paralysis and ataxia, while only 10% of infected animals develop clinical symptoms, which is in agreement with reports of human patients but impractical at the experimental level.…”
supporting
confidence: 82%
“…The ability to further our knowledge of EV71 and to develop effective prophylactic and therapeutic approaches has been severely hampered by the lack of a relevant animal model, a deficit resulting from the limited species tropism of EV71. Experimental infection of rhesus and cynomolgus monkeys has been reported, but their use is limited for ethical and economical reasons (6,15,17,41). Furthermore, EV71-infected monkeys do not develop any typical neurological complications, including flaccid paralysis and ataxia, while only 10% of infected animals develop clinical symptoms, which is in agreement with reports of human patients but impractical at the experimental level.…”
supporting
confidence: 82%
“…Moreover, the presence of EV71 in the blood of wild-type mice, but not miR146a À / À mice, at 3 d.p.i. indicated that viremia occurred only in wild-type mice and that miR-146a knockdown restricted the spread of EV71 [49][50][51] . These data implied that a systemic EV71 infection occurred in wild-type mice but not in miR-146a À / À and IFIT1 (n ¼ 3) (g) in mEV71-infected wild-type or miR-146a À / À mice (mouse tissue samples pooling, n ¼ 4).…”
Section: Resultsmentioning
confidence: 99%
“…The mice were infected with mEV71 through the natural oral route, and the clinical signs, including paralysis, loss of body weight, mortality and even pulmonary edema, were similar to those in human beings 4,[8][9][10][47][48][49][50][51] . However, certain pathological observations in the EV71 infection mouse model were not clinically confirmed in human beings.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, hand, foot and mouth disease (HFMD) has emerged as one of the major epidemic communicable diseases in children in Asian-Pacific countries (1)(2)(3)(4)(5). It manifests as vesicles on the hands, feet, and mouth; herpangina and other cold-like symptoms, and it is occasionally associated with severe encephalitis and cerebromeningitis, which pose a major threat to patients (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%